Overcoming multidrug-resistance in vitro and in vivo using the novel P-glycoprotein inhibitor 1416. Issue 6 (5th October 2012) - Xu, Yan; Zhi, Feng; Xu, Guangming; Tang, Xiaolei; Lu, Sheng; Wu, Jinhui; Hu, Yiqiao
Abstract : MDR (multidrug-resistance) represents a major obstacle to successful cancer chemotherapy and is usually accomplished by overexpression of P-gp (P-glycoprotein). Much effort has been devoted to developing P-gp inhibitors to modulate MDR. However, none of the inhibitors on the market have been successful. 1416 [1-(2, 6-dimethylphenoxy)-2-(3, 4-dimethoxyphenylethylamino)propane hydrochloride (phenoprolamine hydrochloride)] is a new VER (verapamil) analogue with a higher IC50 for blocking calcium channel currents than VER. In the present paper, we examined the inhibition effect of 1416 on P-gp both in vitro and in vivo . 1416 significantly enhanced cytotoxicity of VBL (vinblastine) in P-gp-overexpressed human multidrug-resistant K562/ADM (adriamycin) and KBV cells, but had no such effect on the parent K562 and KB cells. The MDR-modulating function of 1416 was further confirmed by increasing intracellular Rh123 (rhodanmine123) content in MDR cells. Human K562/ADM xenograft-nude mice model verified that 1416 potentiates the antitumour activity of VBL in vivo. RT-PCR (reverse transcriptase-PCR) and FACS analysis demonstrated that the expression of MDR1/P-gp was not affected by 1416 treatment. All these observations suggest that 1416 could be a promising agent for overcoming MDR in cancer chemotherapy.